P.174 The nerve root sedimentation sign on MRI is not only correlated with neurogenic claudication: association with leg dominant mechanical pain. (June 2022) - Newton, B; Huschi, Z; Persad, A; Neuburger, L; Ahmed, U; Cheng, Y; Fourney, D
Abstract : Background: A correlation between the nerve root sedimentation sign (SedSign) and neurogenic claudication has been demonstrated; though it did not account for leg-dominant pain. This study analyzed the utility of SedSign to diagnose leg-dominant pain using validated classification systems. Methods: We retrospectively reviewed prospective data from 367 patients with back or leg pain collected between January 1, 2012 to May 31, 2018. Baseline characteristics included SSPc (Saskatchewan Spine Pathway classification), Oswestry disability index (ODI), visual analogue pain scores (VAS), and EuroQol Group 5-Dimension Self-Report (EQ5D). Inter- and intra-rater reliability for SedSign was 73% and 91%. Results: SedSign was positive in 111 (30.2%) and negative in 256 (69.8%) patients. Univariate analysis showed a correlation between SedSign and age, male sex, ODI, EQ5D, cross-sectional area (CSA) of stenosis, antero-posterior diameter of stenosis, and leg-dominant pain; negative SedSign was correlated with back-dominant pain. Multivariate analysis revealed an association between SedSign and age, male sex, CSA stenosis, and ODI walking distance. The sensitivity, specificity, positive and negative predictive values of SedSign for leg-dominant pain were 33.5%, 83.2%, 77.0%, and 57.3%. Conclusions: SedSign has high specificity but low sensitivity for leg-dominant pain. Despite a similar correlation between SedSign and neurogenic claudication or sciatica, significance was lost on multivariate analysis.